2018
DOI: 10.1103/physrevlett.121.186402
|View full text |Cite
|
Sign up to set email alerts
|

Electron Doping of Proposed Kagome Quantum Spin Liquid Produces Localized States in the Band Gap

Abstract: Carrier doping of quantum spin liquids is a long-proposed route to the emergence of high-temperature superconductivity. Electrochemical intercalation in kagomé hydroxylhalide materials shows that samples remain insulating across a wide range of electron counts. Here we demonstrate through first-principles density functional calculations corrected for self-interaction the mechanism by which electrons remain localized in various Zn-Cu hydroxyl-halides, independently of the chemical identity of the dopantthe form… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…They exhibit strong electronic correlations 31 and even superconductivity 32 . The fact that the number of available strongly correlated Kagome metals is growing significantly is encouraging in view of experimentally realizing our results, and outweighs the difficulties so far encountered in achieving conducting Herbertsmithite materials [33][34][35] .…”
Section: Discussionsupporting
confidence: 64%
“…They exhibit strong electronic correlations 31 and even superconductivity 32 . The fact that the number of available strongly correlated Kagome metals is growing significantly is encouraging in view of experimentally realizing our results, and outweighs the difficulties so far encountered in achieving conducting Herbertsmithite materials [33][34][35] .…”
Section: Discussionsupporting
confidence: 64%
“…Using DFT with Eq. ( 4), Liu et al 212 observed that DFT calculations of n-type doping of the Nd 2 CuO 4 Cuprate superconductor at a low doping concentration of 6.25% (Fig. 20a), predicted an insulating phase due to the formation of an electron polaron with energy in the band gap, localized on the Cu site and accompanied with local lattice distortion.…”
Section: When Isolated Localized Insulating Polarons Coalesce Into a ...mentioning
confidence: 98%
“…The figure is reprinted with permission from Ref. 212 , Copyright (2018) by the American Physical Society.…”
Section: When Isolated Localized Insulating Polarons Coalesce Into a ...mentioning
confidence: 99%
“…These experimental results eliminate all of the jarosites for QSL behavior. However, future investigations into the jarosites could model Wills' 44,46 approach to taking advantage of the large vacancy concentration on the Fe sites and investigate the magnetic properties of doped jarosites to further illuminate their magnetic behavior .…”
Section: Jarosites: Afementioning
confidence: 99%